A pragmatic approach to mobile attention bias modification in a clinical setting - Zhang, Melvyn Weibin (Nanyang Technological University, 2023)
Substance use & alcohol use disorders are highly prevalent globally, and Singapore is no exception. In Singapore, pharmacological approaches are available for the treatment of alcohol use disorders and the maintenance of abstinence, but for other substance use disorders (opioid use, cannabis use and stimulant use), the pharmacological options available are limited. Psychological approaches are paramount in the maintenance of abstinence. Despite the effectiveness of conventional psychological approaches, such as cognitive behavioural therapy for relapse prevention, a significant proportion of individuals still lapse or even relapse. The advances in experimental psychology and increased recognition of cognitive deficits among individuals with addictive disorders, have in turn led to a better understanding of unconscious, automatic biases, that of attention and approach biases that might result in individuals relapsing. Attentional biases are the most fundamental of these unconscious processes, as they refer to how attentional processes are preferentially being allocated to the substance-related stimulus. Despite advances in experimental psychology, there remains several research gaps. These include a lack of synthesized evidence demonstrating that attentional biases are consistently present amongst individuals with substance use disorders and reviews synthesizing the evidence for bias modification in these highly prevalent substance disorders. Whilst the advances in technologies have led to the delivery of these bias modification interventions using web or mobile technologies, there has not been any prior reviews of the published literature, or content analyses of commercial applications. More recently, gamification technologies have been applied to bias modification interventions, but there remains limited understanding of the rationale for gamification, and the gamification strategies that render interventions effective. Most importantly, there have not been any exploration of such interventions amongst an Asian cohort of treatment-seeking individuals with addictive disorders. Also, the interventions that have been used to date for bias modification often are developed by academics and developers but rarely have addressed the needs of patient participants.